Czy Łódź w XIX wieku była miastem kobiet? - Sikorska-Kowalska, Marta (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
The inspiration for the article were contemporary sociological research that lead to the consideration of Lodz – a city of women. Preliminary findings on the interpretation of Lodz as a city of women (the distinction of ”city of woman” and “woman city”, and drawing attention to the numbers and better human capital in women), are the starting point to look at the nineteenth century Lodz from the perspective of the findings. Studies of the nineteenth century Lodz largely correspond to the modern sociological conclusions. It was a city with a strong higher proportion of women, with many feminised professions, which determined its specificity, produced the social problems of one sex. While research over “human capital resources „in the nineteenth century and the first half of the twentieth, fall much to the disadvantage of women. Difficulties in the study were caused by a lack of capacity to analyze the intimate sources, such as letters and diaries, as in Lodz there is no such type of sources. A small number diaries and letters left by woman make no possibility to generalize in the area on the city’s cultural model. Studies on the state of human capital fall for women living in Lodz during the partitions adversely. Characteristically were less educated women, unequal pay, the quality of jobs taken up by women. The demographics of the city and a high level of employment of women in industry and education, as well as the typical problems of professional groups, give grounds to considered Lodz as a feminized city – a city of women.